2016
DOI: 10.1021/acs.jpcc.6b05880
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation, Destruction, and Persistence of Multilayer Dimethyl Methylphosphonate Films during Exposure to O(3P) Atomic Oxygen

Abstract: We present work detailing the oxidative reactivity of the nerve agent simulant dimethyl methylphosphonate (DMMP) with atomic oxygen using time-resolved in situ reflection−absorption infrared spectroscopy (RAIRS) and Xray photoelectron spectroscopy (XPS). When exposed to a supersonic beam containing O( 3 P) with average translational energy of 0.12 eV, thermally annealed DMMP films (less than 50 layers) on single-crystal Au( 111) are observed to react, likely via hydrogen abstraction, and followed by various se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 69 publications
3
9
0
Order By: Relevance
“…In addition to experimental and theoretical work on the thermal decomposition and combustion of these compounds, 11,17,19−21 this work is an extension of previous studies examining oxidative 22,23 and laser destruction 24 of adsorbed chemical nerve agent simulants under ultrahigh vacuum conditions. The oxidative destruction of DIMP and dimethyl methylphosphonate (DMMP) progresses at similar rates and yields oxygen-and carbonyl-containing oligomeric product species.…”
Section: ■ Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to experimental and theoretical work on the thermal decomposition and combustion of these compounds, 11,17,19−21 this work is an extension of previous studies examining oxidative 22,23 and laser destruction 24 of adsorbed chemical nerve agent simulants under ultrahigh vacuum conditions. The oxidative destruction of DIMP and dimethyl methylphosphonate (DMMP) progresses at similar rates and yields oxygen-and carbonyl-containing oligomeric product species.…”
Section: ■ Introductionmentioning
confidence: 93%
“…In addition to experimental and theoretical work on the thermal decomposition and combustion of these compounds, ,, this work is an extension of previous studies examining oxidative , and laser destruction of adsorbed chemical nerve agent simulants under ultrahigh vacuum conditions. The oxidative destruction of DIMP and dimethyl methylphosphonate (DMMP) progresses at similar rates and yields oxygen- and carbonyl-containing oligomeric product species. , Laser desorption and destruction studies of a number of Sarin simulants, (DIMP, DMMP, and diethyl ethylphosphonate), demonstrated lower temperature thresholds for destruction of simulants with relatively larger phosphonate side chains . On the basis of these results, we again expect that the majority of gas-phase products in this study will include a variety of 1, 2, and 3-carbon products generated from the DIMP isopropyl group, with possible incorporation of atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dimethyl methylphosphonate (DMMP, PO 3 (CH 3 ) 3 ) is used in practical applications as a flame retardant. , As a simulant for toxic organophosphorus nerve agents such as VX, sarin, and soman, study of DMMP is also useful to develop sensors for chemical warfare agents and catalysts that drive their decomposition . Materials including alkanethiolate monolayers, carbon nanotubes, and metal oxides have recently been developed for DMMP sensing applications. The study of reactions and decomposition of DMMP on the surfaces of various metal oxides and oxide supported catalysts such as metal nanoparticles, both at room and elevated temperatures, has been an active area of research for over 2 decades. Additionally, multiple studies have demonstrated oxidative and plasma-mediated decomposition of DMMP. To assist in interpreting the decomposition mechanisms of DMMP on various heterogeneous catalysts, a number of computational studies of the electronic structure and gas phase unimolecular decomposition pathways of DMMP have recently been performed. …”
Section: Introductionmentioning
confidence: 99%
“…Most of the experimental details described here are identical to those used in a recent paper on the analogous reaction between O­( 3 P) and DMMP films . One difference, however, is in the method for simulant film deposition.…”
Section: Methodsmentioning
confidence: 97%